Spectrum of breast diseases in a teaching hospital in al najaf - AL-SARRAF, Salem A.H. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: the morphological features of the brest undergoes substantial change between early adolescene and menopause which may result in fibrocystic changes.